Single-Trial Mechanisms Underlying Changes in Averaged P300 ERP Amplitude and Latency in Military Service Members After Combat Deployment - Trongnetrpunya, Amy; Rapp, Paul; Wang, Chao; Darmon, David; Costanzo, Michelle E.; Nathan, Dominic E.; Roy, Michael J.; Cellucci, Christopher J.; Keyser, David (Frontiers in Human Neuroscience, 2019)
Abstract Attenuation in P300 amplitude has been characterized in a wide range of neurological and psychiatric disorders such as dementia, schizophrenia, and posttraumatic stress disorder (PTSD). However, it is unclear whether the attenuation observed in the averaged ERP is due to the reduction of neural resources available for cognitive processing, the decreased consistency of cognitive resource allocation, or the increased instability of cognitive processing speed. In this study, we investigated this problem by estimating single-trial P300 amplitude and latency using a modified Woody filter and examining the relations of amplitudes and latencies from the single-trial level to the averaged ERP level. ERPs were recorded from thirty military service members returning from combat deployment at two time points separated by 6 or 12 months. A conventional visual oddball task was used to elicit P300. We observed that the extent of changes in the within-subject average P300 amplitude over time was significantly correlated with the amount of change in three single-trial measures: 1) the latency variance of the single-trial P300 (r=-0.440, p=0.0102), 2) the percentage of P300-absent trials (r=-0.488, p=0.005), and 3) the consistent variation of the single-trial amplitude (r=0.571, p=0.0022). These findings suggest that there are multiple underlying mechanisms on the single-trial level that contribute to the changes in amplitudes seen at the averaged ERP level. With growing explorations into objective electrophysiologically-derived biomarkers, single-trial analysis may therefore serve as a valuable approach to assess cognitive processing and mental health.